FORMATION OF THE INVESTMENT ENVIRONMENT IN THE DEVELOPMENT OF THE DIGITAL ECONOMY OF THE REPUBLIC OF UZBEKISTAN (International Conference on Economics, Finance, Banking and Management, 2025)
Ushbu maqolada mamlakatimiz iqtisodiyotiga kiritilayotgan investitsiyalar hajmini oshirishning iqtisodiy omillari va investitsiya muhitini shakllantirish masalalari muhokama qilinadi.